Nitrative Stress and Tau Accumulation in Amyotrophic Lateral Sclerosis/Parkinsonism-Dementia Complex (ALS/PDC) in the Kii Peninsula, Japan - Hata, Yukiko; Ma, Ning; Yoneda, Misao; Morimoto, Satoru; Okano, Hideyuki; Murayama, Shigeo; Kawanishi, Shosuke; Kuzuhara, Shigeki; Kokubo, Yasumasa (Frontiers in Neuroscience, 2018)
Objective: The Kii peninsula of Japan is known to be a high incidence area of amyotrophic lateral sclerosis/parkinsonism-dementia complex (Kii ALS/PDC) with tauopathy. Nitrative stress and oxidative stress on ALS/PDC and their relationship to tau pathology were clarified. Methods: Seven patients with Kii ALS/PDC (3 males and 4 females, average age 70.7 years, 3 with ALS, 2 with ALS with dementia, and 2 with PDC) were analyzed in this study. Five patients with Alzheimer’s disease and five normal aged subjects were used as controls. Immunohistochemical analysis was performed on formalin-fixed, paraffin-embedded temporal lobe sections (the hippocampal area including hippocampus, prosubiculum, subiculum, presubiculum and parahippocampal gyri) using antibodies to detect phosphorylated tau (anti-AT-8), nitrated guanine (anti-8-NG), anti-iNOS, anti-NFκB, and oxidized guanine (anti-8-OHdG) antibodies. Results: Most hippocampal neurons of Kii ALS/PDC patients were stained with anti-8-NG, anti-iNOS, anti-NFκB, and anti-8-OHdG antibodies and some AT-8 positive neurons were co-stained with anti-8-NG antibody. The numbers of 8-NG positive neurons and 8-OHdG positive neurons were greater than AT-8 positive neurons and the number of 8-NG positive neurons was larger in patients with Kii ALS/PDC than in controls. Conclusion: Nitrative and oxidative stress may take priority over tau accumulation and lead to the neurodegeneration in Kii ALS/PDC.